2016
DOI: 10.1111/psyg.12212
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between group and personal rehabilitation for dementia in a geriatric health service facility: single‐blinded randomized controlled study

Abstract: Group rehabilitation for dementia is more effective for improving cognitive function and global severity of dementia than personal rehabilitation in Roken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…Previous studies have shown that greater interaction with others results both in greater cognitive function and a lower incidence of dementia. 26,27 Therefore, it is expected that increased social interaction for facility residents who do not often experience contact with others will provide strong cognitive stimulation. During the intervention program, it was difficult to completely exclude elements of interpersonal contact; however, this point has been a long-standing problem in intervention studies targeting cognitive function and future examination is required.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that greater interaction with others results both in greater cognitive function and a lower incidence of dementia. 26,27 Therefore, it is expected that increased social interaction for facility residents who do not often experience contact with others will provide strong cognitive stimulation. During the intervention program, it was difficult to completely exclude elements of interpersonal contact; however, this point has been a long-standing problem in intervention studies targeting cognitive function and future examination is required.…”
Section: Discussionmentioning
confidence: 99%
“…The Mini-Mental State Examination (MMSE) was conducted at baseline and was used to quantitatively assess the severity of cognitive impairment. The MMSE has a satisfactory reliability, although only lower levels of sensitivity for mild degrees of dementia were found (Tombaugh & McIntyre, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…In order to meet the multi-faceted needs of people with dementia, also with respect to the dementia-related lack of initiative and motivation, group rehabilitation may have unique advantages beyond those achievable through individual rehabilitation. Group rehabilitation for dementia is more effective for improving cognitive function and global severity of dementia than personal rehabilitation (Tanaka et al, 2017). In a recent systematic mixed studies review of the effect and importance of physical activity on behavioural and psychological symptoms in people with dementia, the common themes across the qualitative studies were the importance of physical activity being 'socially rewarding' (Junge, Ahler, Knudsen, & Kristensen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Group‐based non‐pharmaceutical interventions are expected to promote success through social interaction [17,18] and have been applied in several disorders such as neuropsychiatric diseases including PD [19], traumatic brain injury [20], stroke [21], dementia [22], schizophrenia [23], depression [24], Huntington's disease [25] and multiple sclerosis [21]. Most of the group trainings are designed for cognitive rehabilitation or education since group‐based interventions in a community setting can promote communication amongst participants and encourage productive social engagement [18,26].…”
Section: Discussionmentioning
confidence: 99%